Analysis Quality of Service from Internet Protocol Television (IPTV) Service - Aiman Mobiu; Dr. Widyawan; Rudy Hartanto (Institute of Advanced Engineering and Science, 2012)
IPTV was convergency product between broadcasting, telecommunication and information technology because gave multimedia service such TV broadcasting, video, audio, text, and data that transmitted by using IP protocol. IPTV service had better quality than conventional TV, such as voice over internet protocol (VoIP), data (internet), and video on demand (VoD). This research had purpose to analyze QoS (delay, jitter, MOS and throughput) from IPTV service such as VoIP, internet (HTTP, FTP), and IPTV in the simulation. The QoS resulted from simulation will be compared with standard ITU-T. The result showed bandwidth requirement for downlink and uplink from the services for VoIP 50 kbps, internet 54 kbps, and the IPTV service 6.5 Mbps. The QoS result showed that used bandwidth less than 15 Mbps, resulted jitter and delay that can not tolerated or QoS more than 250 ms and MOS less than 2. The QoS resulted from queue method had applied on the node DSLAM with bandwidth 8 Mbps, only can decreased the value of delay and jitter as 50% - 65% at VoIP and internet services. PQ method became one of the queue method that can be optimalizing of QoS eventhough only decreased the jitter 10%.DOI: http://dx.doi.org/10.11591/ij-ict.v1i2.594